Carbon Sequestration through Soil Organic Carbon Pool under Different forests Covers in Chamoli District of Uttarakhand - Negi, S. S.; Gupta, M. K. (Indian Forester, 2012)
A study was conducted to estimate soil organic carbon pool (SOC) in three land uses viz. forests, horticulture and grassland in Chamoli district. Under forests land use, soil organic carbon pool was estimated in deodar (Cedrus deodara), quercus (Quercus leucotrichophora), chir (Pinus roxburghii), silver fir and spruce (Abies pindrow and Picea smithiana) and miscellaneous forests. Under horticulture land use SOC was estimated in mango orchards and under grass land SOC was estimated. Soil organic carbon pool under deodar was maximum (121.81 t ha-1) followed by Silver fir and Spruce (113.05 t ha1), Quercus (105.52 t ha-1), Chir (56.73 t ha-1) and the least was under miscellaneous (52.48 t ha-1). Forests of Chamoli district have 3,75,98,188.32 tones (37.59 million tons) and horticulture land use have 0.83 million tones, SOC pool in the soils. SOC pool under forests, grassland and horticulture were compared through ANOVA, SOC pool between forests, grassland and horticultures, were statistically significant different.